2021
DOI: 10.1088/1755-1315/677/3/032037
|View full text |Cite
|
Sign up to set email alerts
|

Food pectin-containing phytocompositions as the basis of functional herbal teas

Abstract: Tea drinks are the most common type of food products for therapeutic and preventive nutrition. This article is about the results of research on pectin-containing phytocompositions as the basis of functional herbal teas. Selected samples of medicinal raw materials: Acorus calamus, Elecampane, Eleutherococcus, Polýgonum aviculáre, oregano, St. John’s wort, motherwort, arrow, dill, Bidens tripartita L., purple Echinacea, dioecious nettle, peppermint, plantain large, aronia, hawthorn, Rosehip, marigold medicinal, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The results of our research have shown that quinoa leaves of Russian selection may be used as natural sources of antioxidant substances in the production of functional products, in particular herbal teas and beverages [22,23,24].…”
Section: Fig 2 Chemical Composition Of Dried Quinoa Leavesmentioning
confidence: 89%
“…The results of our research have shown that quinoa leaves of Russian selection may be used as natural sources of antioxidant substances in the production of functional products, in particular herbal teas and beverages [22,23,24].…”
Section: Fig 2 Chemical Composition Of Dried Quinoa Leavesmentioning
confidence: 89%